Organometallics in Process Chemistry - Colacot, Thomas J.; Sivakumar, Vilvanathan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume gives an overview of the applications of organometallic chemistry in process chemistry relevant to the current topics in synthetic chemistry. This volume starts with an introduction on the historical development of organometallics in process chemistry and is followed by chapters dealing with the last five years' development in various organometallic reaction types such as the challenging cross coupling process, construction of 3.1.0 bicycles, pressure and transfer hydrogenations of historically challenging compounds such as esters, utilization of carbon dioxide for making organic compounds by flow process, drug synthesis and metal detection and scavenging in the finished APIs. A chapter by Colacot et.al., is also devoted to the process development and structural understanding of organometallic catalysts with particular emphasis to LnPd(0) catalysts. An academia - industry collaborated chapter on the use of water as a solvent for organometallic processes is included in this book. .
Organometallic Process Chemistry: A historical snapshot -- Atom Economical Process for LnPd(0) Based Precatalysts -- Cross Coupling Reactions of Heteroatomic Electrophiles -- Transfer hydrogenation -- Organometallic approaches to 3.1.0 bicycles in process chemistry -- The Oxygen Effect in Heteromultimetallic Catalysis: Oxygen Bridged Catalysts for Olefin Polymerization Process -- Sodium acrylate from Ethylene and CO2 via a continuous flow process -- Application of Organometallic Catalysts in API Synthesis -- Organometallic Processes in water -- Meeting metal limits in Pharmaceutical Processes.
Keywords: Organometallic chemistry .; Chemistry, Technical; Catalysis; Green chemistry; Organometallic Chemistry; Industrial Chemistry; Catalysis; Green Chemistry